2016
DOI: 10.1186/s12891-016-1318-y
|View full text |Cite
|
Sign up to set email alerts
|

The Scottish Early Rheumatoid Arthritis (SERA) Study: an inception cohort and biobank

Abstract: BackgroundThe Scottish Early Rheumatoid Arthritis (SERA) study is an inception cohort of rheumatoid (RA) and undifferentiated arthritis (UA) patients that aims to provide a contemporary description of phenotype and outcome and facilitate discovery of phenotypic and prognostic biomarkersMethodsDemographic and clinical outcome data are collected from newly diagnosed RA/UA patients every 6 months from around Scotland. Health service utilization data is acquired from Information Services Division, NHS National Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
(30 reference statements)
0
23
0
Order By: Relevance
“…The SERA study is a national prospective inception cohort of patients with new RA or undifferentiated arthritis, together with age-gender matched controls [ 50 , 51 ]. We used 67 SERA patients for the discovery/validation phases (plus 34 healthy controls) and an additional 19 patients from an independent cohort, who were enrolled in a blinded validation study (demographic and clinical characteristics are shown in Additional file 1 : Tables S2–S4).…”
Section: Methodsmentioning
confidence: 99%
“…The SERA study is a national prospective inception cohort of patients with new RA or undifferentiated arthritis, together with age-gender matched controls [ 50 , 51 ]. We used 67 SERA patients for the discovery/validation phases (plus 34 healthy controls) and an additional 19 patients from an independent cohort, who were enrolled in a blinded validation study (demographic and clinical characteristics are shown in Additional file 1 : Tables S2–S4).…”
Section: Methodsmentioning
confidence: 99%
“…Data were obtained from the Scottish Early Rheumatoid Arthritis (SERA) inception cohort, which prospectively recruited patients with new-onset RA and undifferentiated arthritis (≥1 swollen joint) between 2011 and 2015 attending rheumatology centres across Scotland. 15 Participants in SERA were treated by their usual rheumatology team as per standard clinical practice, independent of their participation in the cohort. This current study evaluated participants in SERA who fulfilled the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) 2010 criteria for RA 16 at the baseline visit.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with an alternative autoimmune rheumatic diagnosis at baseline, patients whose diagnosis was revised to another rheumatic disease during follow-up or patients who had previously received any DMARD were excluded. 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of human samples for cohorts 1, 3 and 4 was approved by the South East Scotland Bioresource NHS Ethical Review Board (Ref 15/ES/0094). Ethical permission to collect samples donated to the SERA inception (cohort 2) was approved by the West of Scotland Local Research Ethics Committee (Ref 10/S0703/4) as previously described (10). Informed consent was obtained from all study participants prior to sample collection.…”
Section: Ethical Review and Donor Selection Criteriamentioning
confidence: 99%